2000
DOI: 10.1108/01443570010304260
|View full text |Cite
|
Sign up to set email alerts
|

Environmental management systems in the New Zealand plastics industry

Abstract: This paper considers the links between quality management systems and environmental management systems. In particular, how firms use their experience with the former to develop the latter. Case studies of seven plastic manufacturers in New Zealand found a high degree of applicability of TQM experiences. Areas most likely to be transferred were people practices, involvement of customers and suppliers, adopting a preventative approach or culture, and strict waste management control. At the current stage of devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 15 publications
(14 reference statements)
1
52
0
2
Order By: Relevance
“…EMS adoption creates increasing returns to learning as skills and knowledge accumulate through learning-by-doing and learning-by-using (Arrow, 1962). Firms with quality management routines in place have already acquired relevant skills and knowledge during implementation and use, which familiarize management and lower the cost of putting a similar system in place (Corbett and Cutler, 2000;Rondinelli and Berry, 2000;Darnall, 2001). Existing management routines are leveraged to cover new areas rather than pursuing the development of totally new practices.…”
Section: The Lock-in Of Emsmentioning
confidence: 95%
“…EMS adoption creates increasing returns to learning as skills and knowledge accumulate through learning-by-doing and learning-by-using (Arrow, 1962). Firms with quality management routines in place have already acquired relevant skills and knowledge during implementation and use, which familiarize management and lower the cost of putting a similar system in place (Corbett and Cutler, 2000;Rondinelli and Berry, 2000;Darnall, 2001). Existing management routines are leveraged to cover new areas rather than pursuing the development of totally new practices.…”
Section: The Lock-in Of Emsmentioning
confidence: 95%
“…QM standards predated the environmental standards, with the first ISO 9001 being launched in 1987 and the first ISO 14001 in 1996, and it likely that QMS predates EMS in many companies. Several authors also found that QMS are beneficial for the introduction of EMS (Borri and Boccaletti, 1995;Corbett and Cutler, 2000;King and Lenox, 2001;Klassen and McLaughlin, 1993;Lawrence et al, 1998;Molina-Azorín et al, 2009;PereiraMoliner et al, 2012;Theyel, 2000;Wiengarten and Pagell, 2012;Yang et al, 2010;Zhu et al, 2013). No articles in this theme focused on the ease of QMS implementation once EMS is implemented.…”
Section: Level Of Focus (Qm)mentioning
confidence: 99%
“…Most articles included in this theme deal with how the QM practices can be used to support the introduction of environmental management. Bergenwall et al, 2012;Borri and Boccaletti, 1995;Corbett and Cutler, 2000;Craig and Lemon, 2008;Curkovic et al, 2000;Giancarlo, 2005;Isaksson and Garvare, 2003;King and Lenox, 2001;Klassen and McLaughlin, 1993;Kuei and Lu, 2013;Lawrence et al, 1998;Molina-Azorín et al, 2009;PereiraMoliner et al, 2012;Rusinko, 2005;Ruzevicius et al, 2004;Stevens et al, 2012;Theyel, 2000;Wiengarten and Pagell, 2012;Yang et al, 2010;Yang et al, 2011;Zairi, 2002;Zhu et Besseris, 2012;Rothenberg et al, 2001;Sakao et al, 2004;Zhang et al, 1998;Zhou and Schoenung, 2003;Zhou and Schoenung, 2007 IV. Supporting stakeholder management and customer focus (8 articles)…”
Section: Theme III E Supporting Integration Of Sustainability Considementioning
confidence: 99%
“…For instance, some researchers suggest the development of EMSs may parallel the establishment of other well known management programmes, such as total quality management (TQM). TQM programmes are often based on the Deming model of quality management, which consists of four phases: Plan, Do, Check and Act (Collins, 2000;Corbett and Cutler, 2000). Similarly, Sheldon and Yoxon (1999) divided the typical structure of EMS specifications into four components: (1) Setting up; (2) Planning; (3) Doing; and (4) Management review.…”
Section: Different Ems Approachesmentioning
confidence: 98%